Exploring Metacognitive Awareness: Theories of Consciousness, Self-Awareness, and Cognitive Processes - Akram, Muhammad; Aslam, Muhammad Tayyab; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
Metacognitive awareness is the ability to reflect upon one's own thinking, experience, and environment. Self-awareness, or the ability to recognize oneself as an individuated self and introspect upon one's own feelings, ideas, and behavior, is a master dimension of consciousness. The argument in this research addresses theories of consciousness, brain origins, and the emergence of self-awareness as it seeks to grasp identity, cognition, and the subjective quality of experience. The relationship between higher-level cognitive processes such as memory, perception, and decision-making and consciousness is also studied to build an impression of how the human brain works.